Introduction of a penicillin allergy de-labelling program with direct oral challenge and its effects on utilization of beta-lactam antimicrobials: a multicenter retrospective parallel cohort study - Mir, Adhora; Lanoue, Derek; Zanichelli, Veronica; van Walraven, Carl; Olynych, Timothy; Nott, Caroline; MacFadden, Derek (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Self-reported penicillin allergy labels are common and often inaccurate after assessment. These labels can lead to reduced use of first-line beta-lactam antibiotics and worse outcomes. We measured the impact of a previously performed inpatient proactive systematic penicillin allergy de-labelling program on subsequent antibiotic use. This prior program included assessment, risk-stratification, and low risk direct oral amoxicillin challenge. Methods We performed a retrospective comparison of parallel cohorts from two separate tertiary care hospital campuses in Ottawa, Canada across two penicillin de-labelling intervention periods across April 15th to April 30th, 2021, and February 15th to March 8th, 2022. Outcomes, including penicillin allergy labelling and antibiotic use, were collected for the index admission and the subsequent 6-month period. Descriptive statistics and multivariate regression analyses were performed. Results A total of 368 patients with penicillin allergy label were included across two campuses and study periods. 24 (13.8%) patients in the intervention groups had sustained penicillin allergy label removal at 30 days from admission vs. 3 (1.5%) in the non-intervention group (p < 0.001). In the 6-months following admission, beta-lactams were prescribed more frequently in the intervention groups vs. the non-intervention groups for all patients (28 [16.1%] vs.15 [7.7%], p = 0.04) and were prescribed more frequently amongst those who received at least one antibiotic (28/46 [60.9%] vs.15/40 [37.5%], p = 0.097). In a multivariate regression analysis, the intervention groups were found to be associated with an increased odds of beta-lactam prescribing in all patients (OR 2.49, 95%CI 1.29–5.02) and in those prescribed at least one antibiotic (OR 2.44, 95%CI 1.00–6.15). No drug-related adverse events were reported. Conclusions Proactive penicillin allergy de-labelling for inpatients was associated with a reduction in penicillin allergy labels and increased utilization of beta-lactams in the subsequent 6-months.